2015
DOI: 10.3897/jhr.47.6804
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific variations in the venom peptidome of the ant Odontomachus haematodus (Formicidae: Ponerinae) from French Guiana

Abstract: Ant venoms are complex cocktails of toxins employed to subdue prey and to protect the colony from predators and microbial pathogens. Although the extent of ant venom peptide diversity remains largely unexplored, previous studies have revealed the presence of numerous bioactive peptides in most stinging ant venoms. We investigated the venom peptidome of the ponerine ant Odontomachus haematodus using LC-MS analysis and then verified whether the division of labor in the colonies and their geographical location ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…The venom of bees, wasps, and ants (Hymenoptera) is a complex mixture of hydrocarbons, salts, sugars, biogenic amines, alkaloids, free amino acids, formic acid, proteins, peptides, and other bioactive compounds (Aili et al., ; Santos, Pieroni, Menegasso, Pinto, & Palma, ; Touchard et al. ; Touchard, Dejean, Escoubas, & Orivel, ). Pioneering studies have demonstrated that the venoms of stinging ants are mostly composed of small peptides, similarly to other venomous animals (Aili et al., ; Touchard et al., , , ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The venom of bees, wasps, and ants (Hymenoptera) is a complex mixture of hydrocarbons, salts, sugars, biogenic amines, alkaloids, free amino acids, formic acid, proteins, peptides, and other bioactive compounds (Aili et al., ; Santos, Pieroni, Menegasso, Pinto, & Palma, ; Touchard et al. ; Touchard, Dejean, Escoubas, & Orivel, ). Pioneering studies have demonstrated that the venoms of stinging ants are mostly composed of small peptides, similarly to other venomous animals (Aili et al., ; Touchard et al., , , ).…”
Section: Introductionmentioning
confidence: 99%
“…; Touchard, Dejean, Escoubas, & Orivel, ). Pioneering studies have demonstrated that the venoms of stinging ants are mostly composed of small peptides, similarly to other venomous animals (Aili et al., ; Touchard et al., , , ). However, a wide variety of proteins has also been described in the venom of different species of ants (Touchard et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Small soldiers such as nasutoids usually rely mainly on the chemical weapons produced by their large front gland, whereas large-jawed soldiers produce less defensive secretion 6,30,31 . www.nature.com/scientificreports/ Termites also produce significantly more defense fluid than other social insects, such as ants, due to differences in the mechanism of action 32,33 . These chemical cues or pheromones are required for various purposes, such as for the recognition of biological processes and caste identification.…”
Section: Discussionmentioning
confidence: 99%
“…Based on examination of the 2D venom landscapes of both Anochetus and Odontomachus, the venom composition and structural diversity appear to be quite dissimilar [56,57]. These closely related ant genera share morphological and behavioral features: they both use their trapjaws to capture prey, followed by a paralyzing sting.…”
Section: Discussionmentioning
confidence: 99%